The Relationship Between Neurotic Leadership Styles, Transformational Leadership, Emotional Intelligence, and Worker Attitudes - Al Bellamy; Allen Bellamy (European Scientific Journal, ESJ, 2016)
This study explored the relationships between neurotic leadership styles, transformational leadership, the emotional intelligence of supervisors, employee job satisfaction, and employee perceptions of leadership effectiveness. The primary objective of this exploratory investigation consisted of determining the extent to which scales measuring neurotic leadership are correlated with extant organizational processes such as leadership and job satisfaction. The study, utilizing a survey was conducted in five law enforcement agencies located in Southeast Michigan. The sample size is 143 police officers. Results of the study reveal significant correlations between the neurotic leadership scales and the other primary factors within the study. It further revealed that the type and strength of the relationships varied across the law enforcement agencies. This latter finding provides strong support for the need to develop empirical studies that integrate psychodynamic and organizational levels analyses.